Kompetensi Pedagogik Guru dalam Mengembangkan Kreativitas Siswa di Sekolah Dasar - Safira, Riski Maulida; Febriandita, Ratih; Khoir, Rifqi Miftahul; Reviani, Risky; Fajaroh, Rofi’ul (Social Science Academic, 2024)
This research aims to determine the pedagogical skills of teachers in developing student creativity at Tarbiyatul Islam Kertosan Elementary School. In this study, one of the factors that influence student creativity is the pedagogicel competencie of teachers in managing student learning. Pedagogical skills as importarit equirement in responding to challeriges, changes, and developments in requirement education Competent teachers will be better able to create an effective, enjoyable learning environment, and better able to manage their classes, as to increase student creativity. Through pedagogical competence, teachers can encourage students to be active learning. This research uses descriptive qualitative methods with interview data collection techniques. Based on previous findings, t shows that pedagogical competence is the ability to manage student learning and develop stucient creativity to actualize their various potentials. This research only focuses on teachers' pedagogical skills in developing student creativity.